2009
DOI: 10.1017/s1478951509000066
|View full text |Cite
|
Sign up to set email alerts
|

Can short hospice enrollment be long enough? Comparing the perspectives of hospice professionals and family caregivers

Abstract: Hospice professionals and caregivers view late-stage admissions differently; they are a crisis for some but not all families. The development of a quick assessment tool for late-stage admissions has the potential for meaningful and effective intervention when time is of the essence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…6,[53][54][55] These findings are particularly relevant to health care professionals working in acute care settings. Recent U.S. data highlight a decrease in overall hospital deaths and an increase in hospice enrollment in the last month of life, tempered by an increase in ICU admission in the final month of life and hospice admission in the final three days of life.…”
Section: Discussionmentioning
confidence: 89%
“…6,[53][54][55] These findings are particularly relevant to health care professionals working in acute care settings. Recent U.S. data highlight a decrease in overall hospital deaths and an increase in hospice enrollment in the last month of life, tempered by an increase in ICU admission in the final month of life and hospice admission in the final three days of life.…”
Section: Discussionmentioning
confidence: 89%
“…Among caregivers to older adults the most studied population has been caregivers to cognitively impaired care recipients, although other conditions have attracted increasing interest, such as cancer [47][48][49], stroke [2,45,[50][51][52][53][54], home-based dialysis [55], heart failure [56], multiple sclerosis [57][58][59], dementia [60], and amyotrophic lateral sclerosis (ALS) [61]. Caregiving research has also emerged from new geographical areas, including Japan [36,62,63], Taiwan [64], China [48,55], and so-called developing countries [65][66][67].…”
Section: The Current State Of Research On Caregivingmentioning
confidence: 99%
“…The limited amount of studies using a salutogenic approach and qualitative design indicated that this procedure unraveled essential data concerning the caregiver situation in a way that another approach and design would probably not have accomplished (Cowley & Billings, 1999;Milberg & Strang, 2004, 2007Potgieter & Heyns, 2006;Pretorius, Walker, & Heyns, 2009;Waldrop & Rinfrette, 2009). Based on the use of salutogenesis in caregiving research, it was assumed that the salutogenic approach combined with an explorative mixed method research agenda (cf.…”
Section: Sense Of Coherence In Caregiving Researchmentioning
confidence: 99%